The antioxidative effects of empagliflozin on high glucose‑induced epithelial-mesenchymal transition in peritoneal mesothelial cells via the Nrf2/HO-1 signaling. Issue 1 (31st December 2022) - Shi, Ping; Zhan, Zhoubing; Ye, Xiaojie; Lu, Ying; Song, Kai; Sheng, Feng; Shen, Huaying; Yin, Peiran
Abstract: High glucose (HG)-induced epithelial-mesenchymal transition (EMT) and oxidative stress play an important role in peritoneal fibrosis, which could be regulated by the nuclear factor erythroid-2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway. This study aimed to investigate whether empagliflozin could inhibit HG-induced EMT and oxidative stress via activating the Nrf2/HO-1 signaling pathway. We used HG-based peritoneal dialysis (PD) solution in rats and HG in human peritoneal mesothelial cells (HPMCs) to induce EMT in vivo and in vitro respectively. The peritoneal structure and function were evaluated by hematoxylin and eosin, Masson's trichrome staining, and the peritoneal equilibrium test. Oxidative stress was measured by assay kits. EMT was analyzed using immunohistochemistry and western blot. The PD rats showed decreased ultrafiltration capacity and increased levels of oxidative stress. Histopathological analysis revealed markedly peritoneal thickening, excessive collagen deposition, increased expression of α-SMA, Collagen-I, and Fibronectin, and decreased expression of E‑cadherin. Empagliflozin significantly ameliorated the aforementioned changes. The protein expression levels of nuclear Nrf2 (N-Nrf2) and HO-1 increased in PD rats, which were further promoted by treatment with empagliflozin. In in vitro experiments, the EMT of HPMCs was induced with 60 mM glucose for 24 h and inhibited by empagliflozin. Empagliflozin suppressed oxidative stress and promoted the protein expression of N-Nrf2 and HO-1 in HG‑stimulated HPMCs, which was reversed by the Nrf2 inhibitor. In conclusion, empagliflozin exerted a protective effect against HG-induced EMT and suppressed oxidative stress in PMCs by activating the Nrf2/HO-1 signaling pathway.